2018
DOI: 10.1210/en.2018-00301
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein 2 Promotes Human Trophoblast Cell Invasion by Inducing Activin A Production

Abstract: Bone morphogenetic protein (BMP) 2 and activin A belong to the TGF-β superfamily and are highly expressed in human endometrium and placenta. Studies have demonstrated that activin A and BMP2 play essential roles in the process of early embryo implantation by promoting human trophoblast cell invasion. However, whether activin A production can be regulated by BMP2 in human trophoblast cells remains unknown. The aim of our study was to determine the effects of BMP2 on activin A production and its role in human tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 41 publications
5
36
1
Order By: Relevance
“…We have previously shown that BMP2 promotes human trophoblast invasion by upregulating N-cadherin expression and activin A production. 14,15 Here we further demonstrate that ID1 is involved in BMP2-induced trophoblast invasion. However, others have shown that Id1 is downregulated during the differentiation of rat Rcho-1 choriocarcinoma cells into trophoblast giant cells, which are thought to be somewhat equivalent to human EVTs.…”
Section: F I G U R E 4 Knockdown Of Id1 or Igfbp3 Abolishes Bmp2-indusupporting
confidence: 63%
See 1 more Smart Citation
“…We have previously shown that BMP2 promotes human trophoblast invasion by upregulating N-cadherin expression and activin A production. 14,15 Here we further demonstrate that ID1 is involved in BMP2-induced trophoblast invasion. However, others have shown that Id1 is downregulated during the differentiation of rat Rcho-1 choriocarcinoma cells into trophoblast giant cells, which are thought to be somewhat equivalent to human EVTs.…”
Section: F I G U R E 4 Knockdown Of Id1 or Igfbp3 Abolishes Bmp2-indusupporting
confidence: 63%
“…13 Expressed at the maternal-fetal interface, BMP2 plays essential roles in endometrial decidualization and EVT cell invasion. [14][15][16] In addition, embryo implantation promotes endometrium decidualization. 17,18 BMP2 secreted by endometrial cells and trophoblast cells may mediate their cooperation during placentation in an autocrine/paracrine manner.…”
Section: Introductionmentioning
confidence: 99%
“…BMP2 is a regulator of SMAD2/3 signalling, influencing the effect of activin receptors, and contributing to increased invasiveness [35,62]. BMP2 induces activin production as well, thus increases the activity of activin receptors [69]. In our experiments, BMP2 mRNA expression was significantly higher during the whole experiment compared to the control.…”
Section: Discussionsupporting
confidence: 43%
“…BMP2 and activin A are expressed in the human endometrium and placenta. BMP2 induces human TB cell invasion by upregulating activin A and inhibin A. BMP2 initiates both canonical SMAD1/5/8 via the ALK3 receptor and non-canonical SMAD2/3 pathways [46]. The same group extended these studies and showed that BMP2 promotes TB cell invasion by upregulating N-cadherin via non-canonical ALK2/3/4-SMAD2/3-SMAD4 signaling [78].…”
Section: Bmp Cascadementioning
confidence: 94%